Pengaruh Locus Of Control Dan Stress Kerja Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Mediasi (Studi Empiris Pada Karyawan Pabrik PT. Tambi) - Tusiana Diyan Pratiwi; Luk luk Atul Hidayati; Muhdiyanto Muhdiyanto (Universitas Muhammadiyah Magelang, 2022)
This study aims to examine and analyze the effect of locus of control, work stress on employee performance with job satisfaction as a mediating variable at PT. Tambi factory employees, Wonosobo Regency. The research method is quantitative, by distributing questionnaires as a data source, and the sampling technique is purposive sampling. The number of samples studied was 100 employees with the criteria of having a working period of one year or more, and being at least 18 years old. The analytical instrument used is multiple regression with the help of SPSS 20.0. The results show that locus of control has a positive and significant effect on performance, job stress has a negative and significant effect on performance, and has a positive and significant effect on job satisfaction, job stress has a negative and significant effect on job satisfaction, job satisfaction mediates locus of control on performance, and job satisfaction mediates work stress on performance.